TEKNIK AKROSTIK DALAM PEMBELAJARAN MENULIS PUISI - Asti Lestina; Dian Indihadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Writing poetry is one of the important language skills to be mastered by elementary school students. However, this skill is often considered difficult because students experience obstacles in exploring ideas, choosing diction, and organizing ideas coherently. This study aims to examine the effectiveness of the acrostic technique in learning to write poetry through a literature study of eleven previous studies. The method used is qualitative research with a descriptive approach through a literature review. The results of the study show that the acrostic technique can significantly improve students' poetry writing skills. This technique makes it easier for students to compose poetry stanzas using the initial letter of a word as a guide. Several studies have also shown that the integration of the acrostic technique with learning media, such as images, audiovisuals, spinwheels, and digital boards, can increase student motivation and participation. Thus, the acrostic technique can be used as an effective alternative strategy in learning to write poetry in elementary schools